Association between postgraduate year 2 residency program characteristics and primary project publication. (15th March 2018) - Swanson, Joseph M.; Shafeeq, Hira; Hammond, Drayton A.; Li, Chenghui; Devlin, John W.
Abstract : Purpose: The association among residency program and research mentor characteristics, program director perceptions, and the publication of the primary research project for postgraduate year 2 (PGY2) graduates was assessed. Methods: Using a validated electronic survey, residency program directors (RPDs) of critical care PGY2 graduates were asked about primary research project publication success, program and research project mentor characteristics, and RPDs' perceptions surrounding project completion. Results: All 55 RPDs surveyed responded; 44 (79%) reported being a research project mentor. PGY2 research project publications in 2011 and 2012 totaled 26 (37%) and 27 (35%), respectively. A significant relationship existed between research project publication and the number of residents in the program ( p < 0.01); the perception among the RPDs that research project publication is important to their employer ( p < 0.01); and the research mentor's funding source ( p = 0.04), employer ( p < 0.01), number of prior publications ( p = 0.01), and research training ( p < 0.01). Variables independently associated with the publication of 2 or more research projects versus no publications included the number of graduates in the PGY2 program (odds ratio [OR], 5.6; p < 0.01), the RPD's perception that the employer valued research project publication (OR, 10.2; p < 0.01), and the number of prior publications by the least-experienced research mentor (OR, 23.5; p = 0.01). The publication of 1 research project versus no research projects was also independently associated with the RPD's perception that the employer valued research project publication (OR, 5.1; p = 0.04). Conclusion: A survey of RPDs of critical care PGY2 residents found that the number of PGY2 residents, the number of publications by the least experienced research mentor, and the perception that publishing the residents' research projects is important to the employer were independently associated with publication rates of residency research projects.